Dipole states and coherent interaction in surface-acoustic-wave coupled phononic resonators - Laetitia Raguin (Nature Portfolio, 2019)
Here, the authors show the capability of a hybrid platform merging surface acoustic waves and coupled mechanical resonators, allowing in a reciprocal manner to coherently control the resonator motion and manipulate surface-acoustic-wave propagation at a sub-wavelength scale.